Europe and the Nordic collective-bargaining model. The complex interaction between Nordic and European labour law (Copenhagen, 2015)
"One of the special features of the Nordic countries is that the determination of wages and working conditions is largely left up to the negotiations between the social partners. The purpose of this report is to illuminate a number of the challenges faced by the labour-law systems of the Nordic countries in the light of an increasingly well-developed European law system. The first part of the report was prepared by Dr. Jur. Jens Kristiansen, the editor-in-chief, and focuses on a number of the general challenges facing the labour-law systems of the Nordic countries in the form of European rules and court decisions. The second part of the report was prepared by various representatives of employer and employee organisations in the Nordic countries and illustrates some of the challenges faced by the social partners in their interaction with the European court system and the way in which these challenges have been addressed in the individual countries."